Viewpoint: How should policy respond to land abandonment in Europe?. (March 2021) - Dolton-Thornton, Nathaniel
Highlights: Researchers need to view land abandonment within the context of rural depopulation. The EU's Common Agricultural Policy provides overly narrow rural support. COVID-19 intensifies the need for diverse, context-specific rural support. The upcoming 2021–27 budget might improve rural support, but only time will tell. Abstract: This article argues that policy responses to land abandonment in Europe must move beyond agriculture-oriented schemes under the purview of the Common Agricultural Policy to incorporate a range of independent, holistic rural development programs.